Implementasi software ACCURATE online di CV. Sumber Tani Kediri - Sugeng (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Accurate Software is an accounting system or program that can process a company's financial activities with the final output being financial reports. The purpose of this research is to find out how the implementation or application of the Accurate Online software in CV. Sumber Tani Kediri. The qualitative descriptive research method was used by the authors in analyzing this research. The results of this study indicate that there are no significant obstacles in the implementation or application of the Accurate software at CV. Sumber Tani. Accurate Online software makes it easy for owners to monitor the company's financial position and control the output of the financial reports they produce. In addition, employees are also assisted in inputting financial reports because the software is easy to use (user friendly). From a taxation point of view, having a system is of course very helpful because it can document sales and purchase transactions which can be accounted for if one day an inspection is carried out by the tax service office (KPP). The effectiveness and efficiency of the application of the software can be felt by CV. Sumber Tani Kediri.